The Arctic Traits Database – a repository of Arctic benthic invertebrate traits - R. Degen; S. Faulwetter (Earth System Science Data, 2019)
The recently increased interest in marine trait-based studies highlights one general demand – the access to standardized, reference-based trait information. This demand holds especially true for polar regions, where the gathering of ecological information is still challenging. The Arctic Traits Database is a freely accessible online repository (https://doi.org/10.25365/phaidra.49; https://www.univie.ac.at/arctictraits, last access: 20 February 2019) that fulfils these requests for one important component of polar marine life, the Arctic benthic macroinvertebrates. It accounts for (1) obligate traceability of information (every entry is linked to at least one source), (2) exchangeability among trait platforms (use of most common download formats), (3) standardization (use of most common terminology and coding scheme) and (4) user-friendliness (granted by an intuitive web interface and rapid and easy download options, for the first time including the option to download a fuzzy coded trait matrix). The combination of these aspects makes the Arctic Traits Database the currently most sophisticated online accessible trait platform in (not only) marine ecology and a role model for prospective databases of other marine compartments or other (also non-marine) ecosystems. At present the database covers 19 traits (80 trait categories) and holds altogether 14 242 trait entries for 1911 macro- and megabenthic taxa. Thus, the Arctic Traits Database will foster and facilitate trait-based approaches in polar regions in the future and increase our ecological understanding of this rapidly changing system.